Mesobiliverdin IXα Enhances Rat Pancreatic Islet Yield and Function - Ito, Taihei; Chen, Dong; Chang, Cheng-Wei T.; Kenmochi, Takashi; Saito, Tomonori; Suzuki, Satoshi; Takemoto, Jon Y. (Frontiers in Pharmacology, 2013)
The aims of this study were to produce mesobiliverdin IXα, an analog of anti-inflammatory biliverdin IXα and to test its ability to enhance rat pancreatic islet yield for allograft transplantation into diabetic recipients. Mesobiliverdin IXα was synthesized from phycocyanobilin derived from cyanobacteria, and its identity and purity were analyzed by chromatographic and spectroscopic methods. Mesobiliverdin IXα was a substrate for human NADPH biliverdin reductase. Excised Lewis rat pancreata infused with mesobiliverdin IXα and biliverdin IXα-HCl (1 – 100 μM) yielded islet equivalents as high as 86.7% and 36.5%, respectively, above those from non-treated controls, and the islets showed a high degree of viability based on dithizone staining. When transplanted into livers of streptozotocin-induced diabetic rats, islets from pancreata infused with mesobiliverdin IXα lowered non-fasting blood glucose levels in 55.6% of the recipients and in 22.2% of control recipients. In intravenous glucose tolerance tests, fasting blood glucose levels of 56 post-operative day recipients with islets from mesobiliverdin IXα infused pancreata were lower than those for controls and showed responses that indicate recovery of insulin-dependent function. In conclusion, mesobiliverdin IXα infusion of pancreata enhanced yields of functional islets capable of reversing insulin dysfunction in type 2 diabetic recipients. Since its production is scalable, mesobiliverdin IXα has clinical potential as a protectant of pancreatic islets for allograft transplantation.